2014
DOI: 10.1016/j.rser.2014.01.085
|View full text |Cite
|
Sign up to set email alerts
|

A review of offshore wind turbine nacelle: Technical challenges, and research and developmental trends

Abstract: The turbine nacelle with traditional wind power generation system is heavy, especially in offshore applications due to the large mass of the power frequency step-up transformer operated at 50 or 60 Hz, and copper conductor generator. For example, the weight and volume of a 0.69/33 kV 2.6 MVA transformer are typically in the range of 6-8 t and 5-9 m 3 , respectively. The weight for a 10 MW direct drive permanent magnet generator is about 300 t. These penalties significantly increase the tower construction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 94 publications
0
60
0
Order By: Relevance
“…They were also the first to deploy their own fleet of tailor-made ships for installation of offshore wind turbines, reducing installation times. They are, lastly, in the process of developing their own proprietary voltage source converter based HVDC technology (Islam et al, 2014). One study called Siemens "an exemplar of integration of knowledge management and innovation management" (Goh, 2005) and concluded that "for several decades, Siemens has enjoyed an internationally enviable reputation in world-class innovations."…”
Section: 3% (Siemens Energy) 4%mentioning
confidence: 99%
See 2 more Smart Citations
“…They were also the first to deploy their own fleet of tailor-made ships for installation of offshore wind turbines, reducing installation times. They are, lastly, in the process of developing their own proprietary voltage source converter based HVDC technology (Islam et al, 2014). One study called Siemens "an exemplar of integration of knowledge management and innovation management" (Goh, 2005) and concluded that "for several decades, Siemens has enjoyed an internationally enviable reputation in world-class innovations."…”
Section: 3% (Siemens Energy) 4%mentioning
confidence: 99%
“…Like Vestas, Siemens has shown a proclivity to partnering with a diverse group of corporate and even non-profit entities. In 2005, SWP entered into a research partnership with the American Superconductor Corporation, U.S. Navy, and Northrop Grumman to develop rotors using superconducting field windings (Islam et al, 2014). In 2009, the company also prototyped the world's first ever floating platform, called Hywind, developed jointly with the Norwegian oil and gas company Statoil and built near Karmø (Perveen , 2014).…”
Section: Stakeholder Involvement and Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the DFIGs are well developed and have previously been widely applied in WECS due to their ability to achieve variable speed control with the reduced cost of converter requirements, the use of slip rings and the protection issues in the event of grid faults are the major drawbacks [8]. As a result, the PMSGbased WECSs have gained more popularity and preference over DFIG-based WECSs owing to their advantages such as high energy density, simple control methodology, high reliability, low maintenance cost, and the self-excitation system [1,13,14]. Moreover, direct-driven multipole PMSGs have been adopted to exclude the gearbox, which improves the efficiency of the WT and cuts down the weight of the nacelle Figure 1: The direct-driven PMSG-based WECS [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, direct-driven multipole PMSGs have been adopted to exclude the gearbox, which improves the efficiency of the WT and cuts down the weight of the nacelle Figure 1: The direct-driven PMSG-based WECS [1]. and the operation and maintenance cost of the WT system [3,13,15]. The major challenge associated with WECS in general is the intermittent nature of the wind resource leading to an inconsistent wind power output.…”
Section: Introductionmentioning
confidence: 99%